Effects of a Novel Oral Testosterone Undecanoate on Ambulatory Blood Pressure in Hypogonadal Men. (November 2021) - White, William B.; Dobs, Adrian; Carson, Culley; DelConte, Anthony; Khera, Mohit; Miner, Martin; Shahid, Muhammad; Kim, Kilyoung; Chidambaram, Nachiappan
Background: Testosterone replacement therapies may increase blood pressure (BP) with chronic use but the mechanism is not clear. TLANDO™ is a new oral testosterone undecanoate (TU) under development for the treatment of male hypogonadism. Methods: We studied the effects of the TU at 225 mg twice daily on ambulatory BP (ABP) and heart rate, in 138 men with hypogonadism (mean age, 54 years, 79% white, 48% with hypertension). Ambulatory BP and heart rate and hematologic assessments were obtained at baseline and following 4-months of therapy. Results: Changes from baseline in ambulatory 24-hour, awake, and sleep systolic BP (SBP) of 3.8 ( P < 0.001), 5.2 ( P < 0.001), and 4.3 mmHg ( P = 0.004) were observed post-treatment, respectively. Lesser changes in the diastolic BP (DBP) were observed (1.2 ( P = 0.009), 1.7 ( P = 0.004), and 1.7 mmHg ( P = 0.011) for 24-hour, awake, and sleep, respectively). Hematocrit and hemoglobin were increased by 3.2% and 0.9 g/dL ( P < 0.001), respectively. In those men in the top quartile of changes in hematocrit (range of 6% to 14%), the largest increases in ambulatory SBP (mean, 8.3 mmHg) were observed, whereas the changes in ambulatory SBP in the lower 3 quartiles were smaller (mean, 1.9, 3.3, and 2.1 mmHg in 1st, 2nd and 3 rd quartiles, respectively). Conclusion: These data demonstrate that small increases in ABP occurred following 4 months of the oral TU. For those men whose hematocrit rose by >6%, BP increases were of greater clinical relevance. Hence, hematocrit may aid in predicting the development of BP increases on testosterone therapy. ClinicalTrials.gov identifier: NCT 03868059.